Persepsi Pasien Terhadap Pelayanan Kesehatan Perawat di Ruang Rawat Inap Kelas III Rumah Sakit Imelda Medan Tahun 2013 - helmida barus; Lita Sri Andayani; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACTThis research is deskriftif by using a quantitative approach. The population in this study are all the patients in the inpatient room class III Hospital Imelda and the number of samples as the respondents a total of 65 people.The results showed the category indicator is direct evidence or real nurses are the majority category either as many as 54 people (83.1%), the category of indicators of reliability of nurses is the majority of the categories are good enough as many as 37 people (56.9%), indicator category respond swiftly nurses are the majority category either as many as 28 people (43.1%), indicator categories convinces nurses are the majority category either as many as 25 people (38.5%) and categories of indicators are the majority of nurses empathy categories less well as many as 26 people (40,0%).In order to change the perception of patients who are not good indicators of health care nurses in inpatient hospitals, Imelda, required the efforts of requiring inpatient room nurses in training activities and seminars on health so that knowledge is always growing and developing as well as they can provide a wide range of health information to patients with precise, hospital management need to set policies and measures to deal with the patient's complaint about the persuasive approach to nurse the nurse through the supervision of the head of the room and the awarding of reward.Keywords: perception of the patient, the nurse service